Cross-Cultural Practices in Business and Finance Frameworks and Skills - Sundararajan, Binod; Shkurska, Oksana; Lin, Shannon (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This textbook explains the effects of culture on business and financial practices and introduces students to the cross-cultural and international dimensions of working in global environments, exploring topics across both business and finance. Given that doing business across cultures has become the norm in modern companies, managers must develop and acquire the skills to lead effectively in cross-cultural contexts. This textbook will help you to attain those skills through its practical and situational examples involving countries and regions around the world while learning about the cultural and business practices of people from different backgrounds, ethnicities, diversities, educational levels, and social strata and hierarchies. It covers important aspects of doing business across cultures/countries, such as the role (and importance) of technology adoption, different organizational forms, financial and accounting approaches in different parts of the world, negotiating practices, ethics across the globe, and working and studying abroad. Further, it equips readers with useful knowledge about cross-cultural nuances beyond the usual discussions of high vs. low contexts, power distance, uncertainty avoidance, and such dimensions of cross-cultural interactions. The varied experiences of the authors - having lived and worked in many countries - along with their backgrounds in linguistics, communication, and financial accounting provide unique perspectives not available elsewhere. With its case studies, end-of-chapter exercises, as well as multiple-choice and short-answer questions, this broad, yet thorough textbook will guide you in leading with cultural intelligence. Binod Sundararajan is Professor of Management at the Rowe School of Business, Faculty of Management, Dalhousie University, Canada. Oksana Shkurska is an Assistant Professor at Rowe School of Business, Faculty of Management, Dalhousie University, Canada. Shannon Lin is an Associate Professor of Accounting at the Rowe School of Business, Faculty of Management, Dalhousie University, Canada. .
Chapter 1. Introduction -- Chapter 2. Business First or Culture First? -- Chapter 3. Culture Shock, Work, and Study Abroad. Chapter 4.The Role of Technology in doing business across cultures -- Chapter 5. Accounting Practices -- Chapter 6. Financial Practices -- Chapter 7. Negotiation Practices. .
Keywords: Diversity in the workplace; International business enterprises; Financial engineering; Personnel management; Business ethics; Cross-Cultural Management; International Business; Financial Technology and Innovation; Human Resource Management; Business Ethics